Patterns of pregnancy loss among women living with and without HIV in Brazil, 2008-2018AJOG Global Reports at a Glance - Lanbo Yang, BA; Mary Catherine Cambou, MD; Eddy R. Segura, MD, MPH; Marineide Gonçalves De Melo, MD, PhD; Breno Riegel Santos, MD; Ivana Rosângela Dos Santos Varella, MD, PhD; Karin Nielsen-Saines, MD, MPH (Elsevier, 2022)
BACKGROUND: Pregnancy loss is poorly understood, but infection may be a risk factor. Few studies have evaluated pregnancy loss among women living with HIV in the era of potent combination antiretroviral therapy. OBJECTIVE: We hypothesize that maternal HIV and syphilis infection lead to increased risk of pregnancy loss, including both miscarriage and stillbirth. This study aimed to assess trends and possible predictors of spontaneous miscarriage and stillbirth among women living with HIV in a cohort of nearly 56,000 deliveries at a major referral institution in a city with the highest prevalence of HIV in Brazil. STUDY DESIGN: Data from hospital records for women delivering from January 1, 2008 to December 31, 2018 were reviewed. Rates of stillbirth, miscarriage, and any pregnancy loss were compared using the Pearson chi-square test. Predictors of pregnancy loss were evaluated by robust univariate log-linear Poisson regression using a generalized estimating equations approach. RESULTS: A total of 55,844 pregnancies were included in the analysis, with 54,308 pregnancies from 43,502 women without HIV and 1536 pregnancies from 1186 women living with HIV (seroprevalence of maternal HIV: 2.7%). Overall, 1130 stillbirths (2.0%) and 6558 miscarriages (11.7%) occurred. Any pregnancy loss was similar in both groups (13.8% in women without and 14.1% in women with HIV; P=.733). Stillbirth was higher among women living with HIV (3.4%) than among women without HIV (2.0%; P<.001), but there was no difference in overall miscarriage rates (10.7% in women with vs. 11.8% in women without HIV; P=.188). Women living with HIV had higher miscarriage rates between 12 and 20 weeks than women without HIV (34.8% vs 23.7%; P=.001), likely because of syphilis coinfection. Stillbirth rates were higher for women living with HIV from 2008 to 2014; however, a steady plateau was reached from 2014 to 2018, mirroring stillbirth rates in women without HIV. Maternal HIV infection did not increase the risk of miscarriage (relative risk, 0.90; 95% confidence interval, 0.77-1.05) or any pregnancy loss (relative risk, 1.00; 95% confidence interval, 0.88-1.15), but was associated with stillbirth (relative risk, 1.65; 95% confidence interval, 1.23-2.21). Maternal syphilis was associated with any pregnancy loss (relative risk, 1.24; 95% confidence interval, 1.11-1.38) and stillbirth (relative risk, 3.39; 95% confidence interval, 2.77-4.14), but not miscarriage (relative risk, 0.91; 95% confidence interval, 0.80-1.04). CONCLUSION: In the era of combination antiretroviral therapy, there was no difference in miscarriage rates between women with and without HIV. HIV was associated with stillbirth risk but improved over time. Maternal syphilis was significantly associated with any pregnancy loss and stillbirth in all women. Syphilis is likely the main driver of pregnancy loss in women living with HIV in Brazil.